26th Palc Day 1 Part 13 (Βιβλιοθήκη & Κέντρο Πληροφόρησης ΕΜΠ, 2021)
: Μετά την παρουσίαση της κυρίας Νάντια Τζάτζ από την Τεδοναλισσεβίρ, θα περάσουμε στην παρουσίαση του Χρυσού Χορυκού EBSCO, The Evolution of EBSCO Discovery Service. Η συγκυτής είναι η Μπόνη Βάισμαν, Vice President for Product Management and SAS at EBSCO Information Services. Από την τελευταία χρονιά, έχουμε κάνει πολλές εξετάσεις στις περιοχές αυθεντικής και προσωπικών εργασμών. Συνεχίζουμε να υποστηρίζουμε παραδοσιακές αυθεντικές μέθες, όπως το Open Athens, SAML, Shibboleth, IP και άλλες, αλλά έχουμε επίσης προσθέσει μια δημιουργία που προσθέτει περισσότερους εργασμούς, όπως το Open Athens, SAML, Shibboleth, IP και άλλες, αλλά έχουμε επίσης προσθέτει μια δημιουργία που προσθέτει περισσότερους εργασμούς για τους χρήστες να εξετάσουν τα προϊόντα μας. Προσθέτησαμε τελευταία Google Kasa, η οποία θα δημιουργήσει τους χρήστες να εξετάσουν τα εργασμούς μέσα από έναν χρόνο, 30-χρονια, υποδοχή campus IP. Αυτή η δημιουργία θα υποστηρίζει ότι οι χρήστες θα έχουν πιο εύκολο χρόνο να βρουν και να σχεδιάσουν τα εργασμούς από το Google Scholar. I do want to note that the Google Kasa functionality is completely optional. We didn't opt in any sites and customers are welcome to turn it on if they would like. The next functionality we recently added is the Forgot My Password. The Forgot My Password option will show when a user signs in to EBSCO and if they did forget their password to their MyEBSCO account, you can easily email them a link and they can reset it on the spot. Finally, LMS integration is integration with the campus learning management system. It allows for EBS and EBSCO host to be integrated directly into campus. In the next 12 months, we're also building support for Microsoft and additional social logins. We understand librarians may not want to enable social logins for privacy and troubleshooting reasons, so those would also all be optional. We're also working on improvements to guest access and releasing a Find My Organization service. The Find My Organization service is currently available on the EBSCO mobile app and allows users to find and authenticate to their EBSCO resources that their library provides for them. Our research on our EBSCO.com website showed that the highest number of turnaways came from college age students who are presumably looking for a way to access their EBSCO resources or perhaps they had a professor who told them to use an EBSCO resource and they didn't know they had to go to the library website to find it. We want to ensure that regardless of how a user tries to access, they can easily find and affiliate to their institutional entitlements through EBSCO. This is a screenshot of our LMS integration with Canvas. The goal of our LMS functionality is to allow faculty to add EBSCO content to assignments and reading lists. It also enables students to access the content without needing a secondary login or having to navigate outside of the learning management system and over to EBSCO. We currently support Canvas and have immediate plans to support Blackboard and Moodle, hopefully within the next 12 months. This functionality is supported in the current version of EBS and EBSCO Host, so administrators are welcome to adopt it now. Search is the next area where we're making some large-scale exciting improvements. Our EBS search differentiates itself from the competition due to its relevancy ranking algorithm. Recently, we released functionality that we call the Knowledge Graph into our search engine. It combines the power of subject indexing, the sore eye, and natural language to ensure that users can find the results they're looking for right out of the gate. The Knowledge Graph maps terms to controlled vocabularies to ensure that users will return useful results even if the original search term was not in the results native language or an exact subject term match. Natural language is another area where we're focusing on, as we know EBS is used by a global population of users. EBS search will now map natural language. So, for example, a search for UAV or on-demand aerial vehicle will also automatically provide results for drone and remote-controlled aircraft. This enhancement means that users don't need to be expert searchers to get the results they're looking for. We've already mapped English language terminology and plan on releasing non-English languages over the next few months. The concept map is another way that we are catering to the ways our users may want to search. The concept map is a graphical interface that allows users to see related concepts and build searches. It enables users to draw correlations between topics that they may not have been aware of or had not thought to relate. It is a visual way to discover topics, concepts, and more. Through our user research, we understand that some users prefer a visual to a list-based search, so the concept map caters to that demographic of users. It will be available with the release of the new EBS experience at no additional charge and will also be optional to add. Here's an example of what the concept map looks like in action. You'll notice in the middle my original search term was for Internet of Things. The related terms show up around it in the little bubbles, and I can click on related terms to build a new expanded search in the right-hand panel. As I build that search, the results populate below, and then when I'm ready to see the full list of results from that search, I can launch it back into a traditional EBS result list. The third section I'm going to cover is both the choose and use areas. In action will be a quick review of functionality we have implemented to make it easier for a user to interact with EBS without needing formal training on how to do research. First off, we continue to welcome users to search EBS without needing to personalize. All they need to do is affiliate to their institution whatever method for authentication that the institution chooses. While personalizing does give users the added benefit of being able to save, group, and export results, we understand that not every user wants to personalize, and not every library wants to make that a requirement or even an option for their users. As you can see, the result list looks a lot more modern and has a lot more white space. The white space is important for device responsiveness, as we know users access from a variety of different screen types and sizes. It's also important to accessibility to ensure all different levels of users can access our products. We also built in the ability, as you'll see at the top, to have dual placards. If a result has matches in both the exact match placard as part of full text finder and a research starter, both will show. An enhancement we made to the exact match placard also supports books now in addition to journal titles if you have them indexed in holdings management. Along the road, we're also planning more custom options for placards, which I'll discuss later in the presentation. The peer reviewed indicator will show on the result list for each result that is peer reviewed. We added this so then it's easier for a user to scan the result list and see which results are peer reviewed if they have a requirement to use peer reviewed in an assignment or they value only using scholarly content. We've also moved the filters. In our current EDS experience, as you all know, filters are on the left-hand side of the screen. Filters are going to be moved up to the top by the search box and they'll only be available when the user needs to interact with them. This user will see a little dot in the toolbar where a filter has been applied to remind them that it's applied and if they want to alter their search, they may want to update the filters. Another new functionality we added is the ability to like items from the result list. The heart icon you'll see on results that's highlighted here shows that a user has liked an icon. We chose the heart button and the like terminology because it tested well with users. It's similar iconography to other online platforms and the concept of liking something translates across online platforms as well. If the user is personalized into their folder, the liked items will go to their dashboard. Users will also have the ability to cite, add a result to a project, share and download directly from the result list without having to click into each record to do those tasks. When citing, the user will be able to immediately choose their preferred citation type and easily copy it to a clipboard so they can paste it wherever they need. We are working on functionality to allow users to default to a citation type as we know there's usually a preferred method across each school and we want to make sure a user doesn't have to scroll through the entire list every time they need to cite something. Currently sharing on Google Drive and Google Classroom are supported and optional. They're a setting you can turn on or turn off in EBSCO Admin. Users can also easily create a link to share on other platforms they interact with and we are looking to expand the list of default sharing options and anything we add will be optional like Google. Users will also be able to download a result in various formats for offline viewing. They'll be able to select a format based on what is supported by the result. Instead of the current experience where we have multiple links at the bottom of each result, what we did was we consolidated it into a dropdown. Through user testing we learned that those multiple links can often be confusing to users because they're not sure which is the best one to click on or they're not sure what the different text on each means or any iconography on each. So we chose to consolidate it into a simple Read Now dropdown. If there are no immediate full text options there will also be a dropdown for ways to access whether that's through an ILL form or another type of library request. We'll also note that the dropdown will still honor any settings in EBSCO Admin around the title for links, the number of links set to show and the order in which they show. E-Books will also be able to be viewed and downloaded directly from the result list. This is in addition to other E-Book enhancements we are making such as the ability to download chapters directly from the detail page, the option to download the whole book or just individual chapters if that's the only section that a user needs to interact with. In our new E-Book viewer we also built the ability to search within the E-Book full text so the user can look for exactly the information without having to skim the entire book. The Add to Project option is a new option that we built. The Add to Project correlates to the enhancements we're making to the dashboard. The dashboard is going to be replacing the My EBSCO folders we have today. The dashboard will allow for a user to personalize and organize their projects which is just a grouping whether it be an assignment or a topic they're interested in conducting research on. Any items they like with that heart icon will go into their dashboard. They'll be able to see past searches and more. The dashboard will work on both the new mobile app and the desktop version of EBS so users can add results from any location as long as they are personalized in. The goal is to give an experience similar to other web services that we use to organize information. Think of Spotify, Gmail or Facebook where we can collect and organize all of our information in one place on those platforms. Much of the functionality I outlined might have been stuff you have already seen from demos with your EBSCO sales team or maybe other marketing sessions you attended to learn more. I also want to give a glimpse into functionality we are working to build as we expand our user base for the new EBS experience to more advanced users. We embarked on a robust beta program with over 60 customers in different markets and different regions. We did this to collect feedback on our initial release of the new EBS experience. The beta program was a 10 week collaborative project between customers and EBSCO teams. The goal was to test the interface with both library staff and different types of end users to collect feedback and help EBSCO inform our roadmap. Overall the feedback was incredibly positive and as a side effect it helped us build stronger relationships between customers and our product management and development teams that worked with the betas. The biggest feedback we received was in four different areas. Advanced search, guest access, widgets and customization as well as advanced level catalog functionality for those customers who choose to load their library catalog into EBS. I want to review some of the initial designs in those areas now. I will caveat that all the designs are subject to change as we continue to iterate on the designs and conduct additional testing. Our goal with the patron functionality as we call it is to provide an experience in EBS that allows a user to interact with the library catalog without having to go over to the separate catalog interface, learn that interface and potentially log in again. We want the user to be able to place view and edit holds within EBS to check live availability and also to manage checkouts and finds. We think this makes a more seamless experience and doesn't worry about the user potentially hitting a link dead end or getting confused when they navigate away to a different interface. Advanced search is another area that we're continuing to iterate on. Our current advanced search is the three search boxes with the field code options as well as a variety of limiter and expander options. We're working with librarians and users to understand what they expect in advanced search. We don't just want to rebuild the functionality we have today for the sake of rebuilding it. Some ideas that we have been working on is a customizable search where users can choose to add those additional search boxes if they need it. Otherwise, they can just use the single search box they're used to. Another option that you'll see in the bottom screenshot is the ability to have a link to advanced search. So users can choose to invoke it when they need it, but for the average user, it's not there. Our goal is to create an advanced search that can be invoked by advanced users but does not scare away a basic user who may feel overwhelmed if they logged into EBS and saw multiple search boxes and limiter options that they may not know how to interact with. Widgets are currently used by almost every EBS customer around the world. Our goal is to reinvent widgets so that they're more uniform and something that a library administrator can easily turn on or off without needing to write custom code or contact EBSCO support or a library service engineers. We reviewed all widgets customers are using and are working on rebuilding the most popular ones for the new EBS experience. Placards, as you see in the screenshots, are one of the most popular widgets, so it's one of the areas we're focusing on first. Customers leverage placards to find specific databases or find out information about the library. As you'll notice in the screenshots, the top one is for CINAHL. If a user came in and searched EBS for CINAHL or for Web of Science or for any other specific database, we want to understand that they're most likely looking to go to the database versus seeing a result list where those results might be integrated in. The second common use case for placards is looking for information about the library, including library hours, how to contact the library, where to park at the library, or other basic information. We encourage customers to put an EBS search box on their homepage. Because users are used to seeing a search box and have it answer all their questions on other websites, they expect the same of EBS. We want to make sure that when they ask EBS a question or want to find information, we can respond to those queries, even if it's not the traditional search. LibGuides is another common widget request that we're looking to reinvent. You'll see the updated design in the blue box in the bottom of the screen. The LibGuides customization will have the same look and feel of the new interface, so it will blend in seamlessly. It will also be able to grab the search result and only surface recommended LibGuides if it matches the search result or a topic. As I discussed earlier, the Find My Organization option will allow users to access their EBSCO entitlements from EBSCO.com. In addition to this, we're also working on guest access functionality, like we support today, so users can see a result list after searching EBS without needing to first log in. Through user testing, we've learned that users are more likely to authenticate if they can confirm a result they see will be useful to them ahead of time. And the last thing I want to touch on is how institutions will adopt the new EBS experience. Our goal is to allow customers to both move to the interface when it's ready for them and when they are ready for a doc. We're going to build the functionality in stages so it won't be ready for all customers right off the bat. Our first early adopter basic customers will start migrating later this month. We won't expect customers to adopt before the functionality they currently use is available, and we'll contact them when we think it is ready for them. I also want to note that we understand that there may be better times of the year that are better for customers to migrate, and we'll definitely take that into consideration and help you transition when it's the right time for you. EBS customers will be the first to adopt this new experience, and we're also working on some similar exciting enhancements for EBSco hosts, which will be available next July or August. We've made it very easy to adopt the new EBS experience to make it a seamless transition for libraries. We've built the technology so that data from your existing EBS profiles can be used to populate the new experience, meaning there's no advanced configuration or EBSco admin work needed on the back to build a new profile or create new links. We've also built the functionality so that customers will be allowed to preview before adopting. This preview state means that customers can look at their unique EBS experience, their branding, content, links, and settings on the new UI so they can get familiar with it, train their users, create any materials they want to market the new EDS before they give the final okay to adopt. Once the site's ready to adopt and give EBSco the go-ahead, we can also automatically redirect all permalinks and all URLs to the new experience so there's little work for the library to do in updating links. We're in the process of creating trainings, help materials, and also generic marketing materials that will help make the transition smooth and will give content that the library can repurpose for their users.